Capacity building for post disaster construction and demolition waste management: A case of Sri Lanka. Issue 2 (4th April 2016) - Karunasena, Gayani; Amaratunga, Dilanthi
Abstract : Purpose: – The purpose of this paper is to present a theoretical framework for capacity building in post disaster construction and demolition (C & D) waste management at a national level to address the identified capacity gaps in managing disaster waste resulting from natural hazards. Design/methodology/approach: – Data were gathered through pilot interviews, case studies and expert opinion surveys representing government, non-government and other sector organisations involved in post disaster waste management. Findings: – The study revealed unavailability of a single point of responsibility and provision for disaster waste in existing policies and capacity constraints in prevailing peace time solid waste management practices which were identified as major capacity gaps. Establishment of a regulatory body and enforceable rules and regulations with necessary levels of capacities was identified and presented in a theoretical framework comprising of seven identified areas for capacity building in post disaster waste management. Research limitations/implications: – This study is limited to disaster C & D waste as debris generated from totally or partially damaged buildings and infrastructure as a direct impact of natural hazards or from demolished buildings and infrastructure at rehabilitation or early recovery stages. Waste generated during reconstruction phase of post disaster management cycle is not considered as disaster C & D waste for purposes of this study. Originality/value: – The research enabled analysis of existing capacities and presents approaches for capacity building for identified gaps in post disaster C & D waste management to attain sustainable post disaster waste management for future resilience.